Condoning postwar corruption: how legacies of war prevent democratic accountability in contemporary Southeast Europe. Issue 2 (3rd April 2022) - Lesschaeve, Christophe; Glaurdić, Josip
ABSTRACT: Do voters in postwar societies punish corrupt politicians? Or are their electoral preferences distorted by their own or the candidates' war pasts? We answer these questions by analysing the results of an experiment embedded in a survey of over seven thousand respondents from the countries of Southeast Europe that experienced armed conflict since the 1990s. Our findings show that voters in this region punish corruption harshly, yet are more likely to ignore it for politicians with a military service record. This tendency is, however, conditioned by voters' partisanship and sense of war grievance.